Pemberdayaan Masyarakat Melalui Kegiatan Posdaya Pada Kecamatan Jatinegara Jakarta Timur - Mardi, Mardi (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2018)
This activity aims to empower the community through the Posdaya Approach (Family Empowerment Post in the fields of economics, education, and health). Communities in Jatinegara Subdistrict are heterogenic communities, the environment around them shows a rapidly developing economy, they must be empowered and nurtured so that they have the ability to compete. The activities carried out provide knowledge on how they should be united in the Posdaya, 10 beginner Posdaya have been formed. Posdaya as a center of friendship and village level empowerment activities that are planned where Posdaya will be formed. Hold a meeting to invite the community to form Posdaya and arrange Posdaya Management. In order to design the initial activities of Posdaya in four areas, namely education, and skills, including religion, entrepreneurship and cooperatives, family planning and health, environment, and hygiene and nutritious gardens.